Perceived vs Actual Denture Hygiene Among Complete Denture Wearers: A Clinical Survey in Tripoli, Libya. - Yusra Elfaidy,; Manal Ebribesh,; Elham Salama,; Tasneem Al-Ajili, (AlQalam Journal of Medical and Applied Sciences, 2026)
Edentulism remains a significant global oral health concern. In Libya, where edentulism among adults aged 20 years and above has been reported at 7.6%, complete dentures continue to represent the most common modality for oral rehabilitation. However, understanding hygiene behavior among denture wearers is essential for improving oral health outcomes. This clinical survey aimed to evaluate denture hygiene practices, self-perceived and actual denture hygiene status among complete denture wearers in Tripoli, Libya. A cross-sectional observational study was conducted from August to December 2025 on 62 complete denture wearers recruited by convenience sampling. Participants completed a self-administered questionnaire addressing demographics, denture hygiene habits, and self-perceived hygiene. Clinical evaluation of 98 dentures was performed using a plaque-disclosing solution and assessed with the Budtz-Jörgensen denture plaque index. Data were analyzed in SPSS using descriptive statistics and Chi-square tests. Questionnaire reliability was confirmed with Cronbach's alpha, and inter-examiner agreement was assessed using Cohen's kappa. Statistical significance was set at p < 0.05. Most participants were older females with low educational levels. Although most of them self-reported adherence to favorable denture-hygiene practices and rated their dentures as having good or excellent hygiene, clinical assessment showed that their denture hygiene, especially for upper ones, was largely inadequate, as only 20.4% demonstrated optimal hygiene, while a substantial proportion of participants were classified as unsatisfactory (34.7%) or poor (18.4%). Significant associations were found between denture hygiene status and demographic factors (p < 0.05), as well as key hygiene practices (p < 0.001). In conclusion, denture hygiene among complete denture wearers in Tripoli, Libya, was predominantly suboptimal, revealing a clear discrepancy between self-perceived and clinically assessed hygiene standards. Demographic factors and daily hygiene practices significantly impacted hygiene outcomes. These findings highlighted the need for improved patient awareness and organized, evidence-based denture care education to enhance oral health among denture wearers.